The Effect of Pair Training Program (Pair Training) on Athletes' Passing Accuracy in Sepak Takraw - cintya dewi; Bhayu Billiandri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The purpose of this study was to investigate the effect of the partner drill program on the accuracy of passing the precepts in early age athletes. The low accuracy of the bait due to the lack of variation in the exercise was the main background of this study. The research method used was an experiment with a One-Group Pretest-Posttest design. The research sample consisted of 30 athletes of the Citra Kartika Sepak Takraw Club aged 8–13 years who were determined through purposive sampling techniques. The research instrument used a feeding precision test with a target zone system to measure the accuracy of the direction and control of the ball. Data analysis was carried out using a paired t-test to compare the athletes' abilities before and after the intervention during 12 meetings. The results showed a significant increase in the average score from 26.43 at the pretest to 32.07 at the posttest, with a significance value of $0.000 < $0.05. These findings indicate that paired exercises are effectively able to improve the coordination of movement and the accuracy of athletes' passes. In depth, the program provides hands-on feedback that accelerates the process of improving technique and increases the social engagement and motivation of athletes. In conclusion, paired training programs are an effective training instrument because they offer a realistic and interactive experience, so it is very relevant to be applied in the golden age phase to optimize motor skills and basic sepak takraw techniques holistically.